Network basis of the dysexecutive and posterior cortical cognitive profiles in Parkinson's disease. Issue 6 (29th March 2019) - Lang, Stefan; Hanganu, Alexandru; Gan, Liu Shi; Kibreab, Mekale; Auclair‐Ouellet, Noémie; Alrazi, Tazrina; Ramezani, Mehrafarin; Cheetham, Jenelle; Hammer, Tracy; Kathol, Iris; Sarna, Justyna; Monchi, Oury
Abstract: Background: The dual syndrome hypothesis of cognitive impairment in PD suggests that two cognitive profiles exist with distinct pathological mechanisms and a differential risk for further cognitive decline. How these profiles relate to network dysfunction has never been explicitly characterized. Objective: First, to assess intranetwork functional connectivity while considering global connectivity, and second, to relate network connectivity with measures of the dysexecutive and posterior cortical profiles. Methods: Eighty‐two subjects with idiopathic PD and 37 age‐matched controls underwent resting‐state functional MRI and comprehensive neuropsychological assessment. Intranetwork and global connectivity was compared between groups. Measures of the dysexecutive and posterior cortical profiles were related to network connectivity while considering demographic and disease‐related covariates. Results: PD subjects show decreased connectivity within several cortical networks. However, only the sensorimotor network displayed a loss of connectivity independent of the observed decreased global connectivity. The dysexecutive factor was independently related to increased motor severity, less education, and decreased connectivity in the sensorimotor network. The posterior cortical factor was related to increased age, less education, decreased connectivity in the central executive network, as well as increased connectivity in the temporal network. Conclusions: Our results provide evidence supporting a network‐specific process of degeneration in the sensorimotor network which contributes to the dysexecutive cognitive profile. In contrast, connectivity of the temporal and central executive network is related to the posterior cortical profile, representing a distinct network signature of this syndrome. © 2019 International Parkinson and Movement Disorder Society